2014
DOI: 10.1111/epi.12840
|View full text |Cite
|
Sign up to set email alerts
|

Seizure expression, behavior, and brain morphology differences in colonies of Genetic Absence Epilepsy Rats from Strasbourg

Abstract: SUMMARYObjective: Originally derived from a Wistar rat strain, a proportion of which displayed spontaneous absence-type seizures, Genetic Absence Epilepsy Rats from Strasbourg (GAERS) represent the most widely utilized animal model of genetic generalized epilepsy. Here we compare the seizure, behavioral, and brain morphometric characteristics of four main GAERS colonies that are being actively studied internationally: two from Melbourne (MELB and STRAS-MELB), one from Grenoble (GREN), and one from Istanbul (IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 36 publications
(67 reference statements)
10
51
1
Order By: Relevance
“…Unpublished data. but absent in all NEC rats (Powell et al, 2014) (see below). Environmental conditions may have therefore a significant impact on the expression of the SWD.…”
Section: Why Is Gaers a Robust Model?mentioning
confidence: 88%
See 3 more Smart Citations
“…Unpublished data. but absent in all NEC rats (Powell et al, 2014) (see below). Environmental conditions may have therefore a significant impact on the expression of the SWD.…”
Section: Why Is Gaers a Robust Model?mentioning
confidence: 88%
“…In parallel, we also bred rats from the same outbred Wistar colony in Strasbourg that were free of SWDs and over 5-6 generations we obtained the Non-Epileptic Control (NEC) strain where none of the animals display any seizures (Marescaux et al, 1992a). Both inbred strains have been maintained in Strasbourg and, since 2003, in Grenoble, as well as in Paris, Melbourne, Istanbul and Cardiff (Powell et al, 2014). The GAERS model shares a lot of similarities with another genetic model of absence epilepsy in the rat, the WAG/Rij which was inbred in the United Kingdom, then kept in Rijswijk and later at Nijmegen (The Netherlands) (Depaulis and van Luijtelaar, 2005).…”
Section: The Development Of Gaers and Its Control Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic Absence Epilepsy Rats from Strasbourg (GAERS) is an animal model closely resembling CAE. GAERS not only demonstrate recurrent non-convulsive seizures with bilateral and synchronous spike-and-wave discharges (SWD) characteristic of CAE (Marescaux et al, 1992) but also the anxiety and psychiatric-like phenotypes associated with epilepsy (Bouilleret et al, 2009;Dezsi et al, 2013;Jones et al, 2008;Jones et al, 2010;Marks et al, 2016;Powell et al, 2014; but see also Marques-Carneiro et al, 2014). Similar to CAE, GAERS exhibit altered cognition with increased performance observed in fear conditioning and two-way active avoidance tests (Getova et al, 1997;Marks et al, 2016), performance deficits observed for latent inhibition and extinction of conditioned fear (Marks et al, 2016), and delayed acquisition of spatial reference and working memory in a Morris water maze (Marques-Carneiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%